Charge storage in binder-free 2D-hexagonal CoMoO4 nanosheets as a redox active material for pseudocapacitors. Issue 6 (15th March 2021) - Hussain, Shahid; Khan, Abdul Jabbar; Arshad, Muhammad; Javed, Muhammad Sufyan; Ahmad, Awais; Ahmad Shah, Syed Shoaib; Khan, Mohammad Rizwan; Akram, Shakeel; Zulfiqar; Ali, Shafaqat; ALOthman, Zeid A.; Liu, Guiwu; et al.
Abstract: Binder-free CoMoO4 hexagonal nanosheets have been directly grown on the surface of conductive carbon fabric cloth (CoMoO4 @CFC) as a hybrid electrode material for pseudocapacitors (PCs) with outstanding electrochemical properties. The as-prepared CoMoO4 @CFC sample was structurally and morphologically characterized using various techniques. Microstructure analysis reveals that the hexagonal like 2D structure possesses mesoporous characteristics with abundant electroactive sites as a charge storage host. The CoMoO4 @CFC was evaluated as a positive electrode material for pseudocapacitors, which revealed a maximum specific capacitance of 1210 F/g at 2.5 A/g with exceptional rate capability and outstanding cycling stability of 91% after 10, 000 charge/discharge cycles. The 2D mesoporous hexagonal-like structure provides improved electrolyte movement during charging/discharging process and additional active sites for redox reactions. In addition, the charge storage quantification of diffusion and capacitive charge mechanism was determined by employing Power's law, and accordingly, the CoMoO4 @CFC electrode was attributed to a high capacitive charge value of (80% at rate 2.5 mV/s). Thus, this work specifies simple and cost-effective method to fabricate pseudocapacitors electrode materials with high energy density and improved cyclic life for energy storage devices.